2020
DOI: 10.31460/mbdd.746809
|View full text |Cite
|
Sign up to set email alerts
|

Deneti̇m Alaninda Blokzi̇nci̇r Uygulamalarinin Hari̇talama Yöntemi̇ İle Anali̇zi̇

Abstract: Blockchain technology has a wide scope of applicability for accounting and auditing purposes, separate from Bitcoin or other cryptocurrencies. However, although blockchain technology is identified as a popular topic within the field, there currently exists a lack of consensus on how it will be realistically applied. This paper aims to map the presently existing international auditing literature and offer clarity to an otherwise heterogeneous field. The mapping analysis will aid in examining the underlying them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…In bibliometric analysis, some mathematical and statistical techniques are used to create meaningful data which helps both to organize knowledge in a specific field to better understanding of recent and following research hotspots and to evaluate performance of the nation, institute, journal and author (Wallin, 2005). For example, the Bibliometrix R-Package program is mostly used by the researchers to analyse the collobaration and cooperation network (Aria and Cuccurullo, 2017;Moral Muñoz et al, 2020;Cagle, 2020). Moreover, Web of Science (WoS) database which published by Thomson Reuters, is vastly preferred and accepted database by researchers for bibliometric analysis (Chiu and Ho, 2005;Zhang et al, 2016;Zhang et al, 2019;Cagle, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In bibliometric analysis, some mathematical and statistical techniques are used to create meaningful data which helps both to organize knowledge in a specific field to better understanding of recent and following research hotspots and to evaluate performance of the nation, institute, journal and author (Wallin, 2005). For example, the Bibliometrix R-Package program is mostly used by the researchers to analyse the collobaration and cooperation network (Aria and Cuccurullo, 2017;Moral Muñoz et al, 2020;Cagle, 2020). Moreover, Web of Science (WoS) database which published by Thomson Reuters, is vastly preferred and accepted database by researchers for bibliometric analysis (Chiu and Ho, 2005;Zhang et al, 2016;Zhang et al, 2019;Cagle, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Araştırma sonucunda; denetim kanıtlarının toplanmasının iyileştirilmesindeki yapay zekâ uygulamalarının bilimsel önemi nedeniyle, denetim ofisleri tarafından yapay zekâ teknolojilerine artan bir ilgi olduğu görülmüştür. Cagle (2020), blockchain alanında yapılmış olan çalışmalar üzerinde bibliyometrik bir araştırma yapmış olup Bibliometrix R-Package "Biblioshiny" haritalama yöntemi ile 112 araştırmayı veri olarak kullanmıştır. Araştırma sonucunda bu konuların uluslararası platformlarda giderek önem kazandığı, denetimde blok zincir teknolojisinin benimsenmesini hızlandırmak için ele alınması gereken bir araştırma boşluğu olduğu gibi hususlara ulaşılmıştır.…”
Section: Literatürunclassified
“…The latest control mechanism in blockchain ledgers contains the notion that the user has a comprehensive facility to copy the accounting transaction, ledger and system features that might restrict to alter any transactions (Cangemi and Brennan, 2019). Cagle (2020) in their study found that FinTech and blockchain topic recently has gained augmented worldwide acceptance and separated into diverse research streams such as distributed ledger in the accounting field and continuous audit in the auditing profession, but still there exists a research gap in the field of financial technology in the auditing field.…”
Section: Introductionmentioning
confidence: 99%